Interception of Bean common mosaic virus in bambara groundnut accessions imported from Ghana through RT-PCR - Parameswara, B; Bajaru, Bhaskar; selvi, Karthikai; Sivaraj, N; Pranusha, P; Brahmi, Prathibha; Mangrauthia, S K; Saravanan, L; Chalam, Celia; Anitha, K (Indian Journal of Plant Protection, 2023)
Bambara groundnut (Vigna subterranea) is an African legume with a great nutritional, economic and social potential. Thirty three bambara nut accessions imported from four African countries viz., Ghana, Niger, Tanzania and Uganda were grown in the glass house of ICAR-NBPGR Regional station, Hyderabad for post-entry quarantine growing during Rabi 2020-21. In December 2020, mosaic symptoms were observed on EC 1050874 out of ten accessions imported from Ghana. RNA was extracted from suspected samples and reverse transcribed with Potyvirus genus specific degenerate primers resulted in amplicons of 600 bp. These amplicons were sequenced and NCBI Blast analysis showed 98.9% nucleotide sequence similarity to Bean common mosaic virus (BCMV) cylindrical inclusion protein (CI) sequences available in GenBank. Based on the results, BCMV specific primer was designed covering full length coat protein and partial -3′ non-coding region and resulted in amplicons of 900 bp. Further cloning and sequencing and blast analysis confirmed the association of BCMV with bambaranut imported from Ghana. Phylogenetic tree generated showed close association of BCMV-Ghana isolate with BCMV- (Purerto Rico) and BCMVTZ:KRG2-7 (Tanzania) isolates. The results obtained from phylogenetic study were further supported by the different in silico analysis viz. evolutionary distance analysis, recombination and selection pressure analysis etc. However, till now there is no information available on occurrence of BCMV in bambara groundnut from Ghana. The entry of BCMV isolate from Ghana into India has been prevented.